2011
DOI: 10.5216/rpt.v40i3.15977
|View full text |Cite
|
Sign up to set email alerts
|

Pediculose Do Couro Cabeludo Em Crianças De Creches E Escolas De Manaus, Amazonas, Brasil

Abstract: Head lice infestation is a public health problem, which, though more prevalent in children, may occur in all age groups. From July 2009 to February 2010 a total of 976 children aged 0-12 years who attended four schools and three day-care centers in Manaus, Amazonas State, Brazil, were screened for the presence of head lice. The prevalence rate was 18.5%, with black (X 2 0.05 (1) = 4.655) female children (X 2 0.05(1) = 151.324) with dark hair (X 2 0.05(1) = 9.942) showing the highest prevalence rates. The type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 16 publications
4
18
0
2
Order By: Relevance
“…The monthly distribution of infestation was monitored for three years. School age children seemed to act as reservoirs of this disease 4 and studies have demonstrated that significant variation in occurrence appears among children between the academic and vacation periods in Minas Gerais 3 , 20 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The monthly distribution of infestation was monitored for three years. School age children seemed to act as reservoirs of this disease 4 and studies have demonstrated that significant variation in occurrence appears among children between the academic and vacation periods in Minas Gerais 3 , 20 .…”
Section: Methodsmentioning
confidence: 99%
“…In cases where significant differences between more than two proportions were observed, the data were submitted to angular transformation (p' = arc. sen √p'), followed by multiple comparisons using the Tukey range test 4 , 29 . A 5% level of significance was adopted 29 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations